Advances in Stem Cell Therapy for Leukemia - Tian, Hong; Qu, Qi; Liu, Liming; Wu, Depei (Current Stem Cell Research & Therapy, 2016)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the most effective post remission treatment for leukemia, resulting in lower relapse rates than alternative therapies. However, it is limited by the lack of suitable human leukocyte antigen (HLA) matched donors and high rates of transplant-related morbidity and mortality. Cord blood transplantation (CBT) and haploidentical SCT (haplo-SCT) expand the potential donor pool but are also associated with major complications. Co-infusion of third-party donor stem cells with a CBT/haplo-SCT, which is called “dual transplantation,” has been reported to improve the outcome of HSCT by accelerating hematopoietic reconstitution and reducing the incidence of graft-versus-host disease (GVHD). In addition, infusion of HLA-mismatched donor granulocyte colony-stimulating factor–mobilized donor peripheral blood stem cells after chemotherapy, the so called “microtransplantation”, has been shown to promote the graft–versus-leukemia effect and hasten hematopoietic recovery without amplifying GVHD. Herein, we review recent advances in stem cell therapy for leukemia with a specific focus on dual transplantation and microtransplantation.
Keywords: microtransplantation